PENGARUH EKONOMI INDUSTRI MAKANAN DAN MINUMAN DI INDONESIA TAHUN 2009–2013 - Irma Wijiati; Budi Santosa (Media Ekonomi, 2015)
Food and beverage industry in Indonesia are rapidly followed by the times. To know the development of the food and beverage industry can be seen from market structure, industry concentration and market share in the food and beverage industry in the market firms in Indonesian food and beverage sales. Results based on the total concentration ratio (CR4) is high enough, means that the market structure in the food and beverage industry in 2009-2013 belong in a tight oligopoly. The company with the largest market share in 2009-2013 is PT. Mayora Indah Tbk, PT. Multi Bintang Tbk, PT. Ultra Jaya Milk Industry and Trading Company, Tbk, PT. Tiga Pilar Sejahtera Food Tbk. In the other side, based on the Herfindahl Hirschman Index (IHH), food and beverage industry competition in Indonesia is competitive with high concentration and not competitive. This encourages each behaviour of the companies to undertake strategies against competitors, conduct promotions and innovations. To improve the performance of food and beverage companies to increase sales